Numerical simulation and experimental study on eggshell membrane separation device - Chi, Yuan; Wang, Yong; Li, Mengfu; Ren, Jie; Chi, Yujie (International Journal of Agricultural and Biological Engineering, 2019)
In order to provide theoretical guidance for separating egg membrane from eggshell by using mechanical agitation, CFD was used to explore the flow characteristics in stirred tank, using the Sliding Grid method to deal with the impeller rotational velocity zone in flow field, and using the Euler model to deal with liquid-solid two-phase flow. This study explored the influence of dish-shape bottom or flat-shape bottom, the clearance size between baffle and the side wall, and the axial height of impeller to bottom on suspension state of particles, solids holdup distribution, solid phase velocity and power number by CFD. Simulation results showed that better particles suspension effect in dish-shape tank can reduce particles accumulation at the bottom and power consumption. If there was a small clearance size (S) between the baffle and the side wall of the stirred tank, it would reduce particles accumulation at the bottom, and reduce the power consumption. However, too large S would decrease the suspension height of particles, not only cannot strengthen the main flow, but also lead to most fluid through clearance forming tangential flow, simulation results showed that S=6 mm was perfect. While decreased axial height of impeller (C) to bottom, particles accumulation at the bottom was decreased, but power consumption would increase, simulation results showed that C=H/5 (H is height of liquid surface) was perfect. According to the simulation results, the structure of the stirring tank was optimized. At the same time, the influences of stirring rotational velocity, stirring time, solid-liquid ratio and separating medium temperature on egg membrane recovery were also studied by experiment, and optimal parameter combination of factors was obtained. The experiment results showed while the stirring time was 17.1 min, stirring rotational velocity was 350 r/min, solid-liquid ratio was 1:17 g/mL, the separating medium temperature was 32°C, the membrane recovery rate can reach above 89%. The device improves the recovery and utilization of discarded eggshell, and provides a reference for the solid-liquid two-phase flow and related study. Keywords: liquid-solid two-phase flow, mechanical stirring, field characteristics, eggshell membrane separation DOI: 10.25165/j.ijabe.20191202.3058 Citation: Chi Y, Wang Y, Li M F, Ren J, Chi Y J. Numerical simulation and experimental study on eggshell membrane separation device. Int J Agric & Biol Eng, 2019; 12(2): 173–183.